Profiles of Aggressiveness and Stress in Spanish Adolescents - Cecilia Ruiz-Esteban; Inmaculada Méndez; Juan Pedro Martínez-Ramón; Nuria Antón-Ros; Nelly Gromiria Lagos San Martín (European Journal of Investigation in Health, Psychology and Education, 2025)
Aggressiveness among schoolchildren can be shaped by specific school-related situations that elicit stress. Accordingly, this study aimed to identify differentiated profiles of secondary school students based on the levels of aggressive behavior they exhibit. A further objective was to examine whether various stress-related factors differ significantly across these behavioral profiles. The sample consisted of 386 secondary school students (M = 13.73; SD = 1.14), of whom 52.6% were female. Data were collected using the Aggression Questionnaire (AQ) by Buss and Perry and the School Situation Survey (SSS) developed by Helms and Gable. Latent profile analysis revealed three distinct profiles: (a) students exhibiting high levels of aggressive behavior (Cluster 1), (b) students showing moderate levels of aggressive behavior (Cluster 2), and (c) students displaying low levels of aggressive behavior (Cluster 3). Students in the high-aggression profile reported significantly higher scores on most sources of stress compared to their peers in the moderate and low aggression profiles. From an educational standpoint, these findings underscore the importance of addressing school-related stressors, as they appear to play a critical role in influencing student behavior.